A Survey to Evaluate Zoological Park Visitor's Satisfaction (International Journal of Innovative Research in Engineering & Management, 2021)
Tourism is a significant development driver for financial and  social development, job creation, and poverty alleviation. It  also has a significant responsibility to contribute in encouraging  the state's economic development to be quicker, more  sustainable, and more inclusive. India has the most diverse  terrain and climate, allowing a diverse variety of plants and  animals to thrive. Including its very old cultural history, a  plethora of landmarks, and nature's bounty, Odisha epitomizes  a thriving tourist industry. Zoos have long been popular  meeting places for families and friends, and many individuals  find psychological solace in taking in the natural environment  and engaging with animals. Zoo visitors come to the zoo with  a diverse set of motivations, interests, and knowledge about  animal conservation and environmental problems. The main  goal of this study is to determine the degree of satisfaction of  zoological park visitors at Nandankanan based on several  factors such as communication, visibility, and information  availability. From September to December 2016, data was  gathered from 250 visitors in a random sample utilizing  structured questionnaires. The majority of tourists are pleased  with communication facilities, information availability, and  enclosure, visibility, and guide services. To fulfil the overall  level of satisfaction of tourists, the lot of wildlife, exhibition  services, leisure facilities, and other amenities need to be  improved.
Keywords: Eco-tourism; Nandankanan Zoological Park; Questionnaire Survey; Satisfaction Level; Visitor's Satisfaction